2015
DOI: 10.4238/2015.december.23.11
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and structure in natural populations of Maytenus truncata Reiss, 1861, a medicinal plant vulnerable to extractivism in Bahia State, Brazil

Abstract: Maytenus truncata (Celastraceae) is a plant species widely used in the treatment of ulcers and tumors. Despite the intensive harvest of native specimens in the State of Bahia, northeastern Brazil, there is no information about the genetic variability or structure of this species. Therefore, the goal of this study was to estimate the genetic diversity and population structure of M. truncata based on inter simple sequence repeat (ISSR) molecular markers. The samples comprised specimens from Jequié, Contendas do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…A estratégia de caracterização e seleção de iniciadores como etapa preliminar em estudos genéticos, tem sido adotada em estudos com diferentes espécies, a exemplo da caracterização da diversidade genética em populações naturais de C. heliotropiifolius (Rocha et al, 2016), de Sinopodophyllum hexandrum (Liu et al, 2016) e de Maytenus truncata (Simplicio et al, 2015). Para Croton linearifolius são escassos os estudos genético moleculares e apenas caracterizações iniciais foram disponibilizadas por Rocha (2015) envolvendo marcadores RAPD e ISSR.…”
Section: Resultsunclassified
“…A estratégia de caracterização e seleção de iniciadores como etapa preliminar em estudos genéticos, tem sido adotada em estudos com diferentes espécies, a exemplo da caracterização da diversidade genética em populações naturais de C. heliotropiifolius (Rocha et al, 2016), de Sinopodophyllum hexandrum (Liu et al, 2016) e de Maytenus truncata (Simplicio et al, 2015). Para Croton linearifolius são escassos os estudos genético moleculares e apenas caracterizações iniciais foram disponibilizadas por Rocha (2015) envolvendo marcadores RAPD e ISSR.…”
Section: Resultsunclassified
“…Molecular markers have been used in the assessment of genetic diversity and population genetic structure of species (Craft et al, 2010;Simplicio et al, 2015). The population structure and genetic diversity of Zelkova schneideriana from seven populations were analyzed using two chloroplast regions; the results suggested that Z. schneideriana should be protected by an in situ conservation strategy (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%